Arguing into the digital void? - Winsvold, Marte (Javnost (Ljubljana), 2009)
With the advent of the Internet, numerous online debate options have been created, giving citizens new arenas of political communication where space forexpression is nearly unlimited. However, if online forums shall invigorate the public debate, the arguments published online must reach outside their initial setting. In this article, the position of newspaper-hosted online forums is studied and compared to the position of letters to the editor in thelocal public spheres of four Norwegian municipalities. The forums' visibility to the public and the degree to which they are paid attention to byother media and by local politicians are used as indicators of their position. Only onetenth of the citizens regularly read the online forums, and when referred to in other media or in politics, they have an agenda-reinforcing rather than an agenda-expanding role. The greatest challenges to the online forums' position seem to be the audiences' perceptions of the quality of the discussion, along with the vast amount of contributions which makes them reader unfriendly.
Keywords: Norveška; javna sfera; občine; communication; komuniciranje; mass media; množični mediji; elektronski mediji; internet